Solusi Alternatif Penyelesaian dan Peran Etika Profesi Hukum dalam Konflik Pemotongan Upah Sepihak Jurnalis CNN - Shifa Raisa Parsa; Mega Dewi Ambarwati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The case of unilateral salary cuts experienced by CNN journalists shows clashes in industrial interactions in the media sector. Disputes like this not only affect employee welfare, but also pose risks to the company's reputation and the stability of working relationships. This research aims to identify the main causes of conflict, as well as assess the effectiveness of alternative solutions in resolving disputes (Alternative Dispute Resolution/ADR). In this research, normative and empirical juridical methods are applied, accompanied by data analysis through document review, as well as an assessment of the application of ADR which includes mediation, conciliation and arbitration. Research findings indicate that unilateral wage reductions often occur due to a lack of openness in communication, weak legal protection for employees, and little worker participation in the decision-making process